Fortification of Protein Hydrolyzate of Mujair Fish (Tilapia mossambica) in Enyek-Enyek (Cassava crackers) - Eka Herlina; Farida Nuraeni; Aldi Alhadid (Helium: Journal of Science and Applied Chemistry, 2022)
This study aims to determine the best-enriched formula for tilapia fish using an analysis of chemical and organoleptic characteristics. The research was carried out at the Chemical Laboratory of Pakuan University, Bogor from March to May 2021. The method used was an experimental method with six additional treatments of tilapia protein hydrolyzate, namely 0%, 2.5%, 5%, 7.5%, 10% and 12.5% with 20 semi-trained panelists as replicates. The observed variables consisted of the hydrolyzed protein yield of African catfish, the panelists' preference for color, texture, and taste of geeks, and a proximate test on water content, ash content and insoluble ash in acids, proteins, fats, and carbohydrates. The level of liking was calculated by Friedman Test, after which followed by Bayes Test to find out the best formula with the addition of tilapia fish protein hydrolyzate. The results showed that the addition of tilapia protein hydrolyzate in the research was still considered favorable, but the preferred treatment was the addition of 5% tilapia protein hydrolyzate, from some characteristics such as: better appearance, better texture, taste and aroma 7 (preferred), moisture 6.1% content, ash content 1.9%, acid insoluble ash content 0.17%, protein content 6.2%, and carbohydrates content 84.9%.